2019
DOI: 10.1097/prs.0000000000005212
|View full text |Cite
|
Sign up to set email alerts
|

Matching into Integrated Plastic Surgery: The Value of Research Fellowships

Abstract: Background: Integrated plastic surgery residency applicants sometimes complete research fellowships before residency. The average productivity and the impact of these fellowships on subsequent application to residency are unknown. The purpose of this study was to provide objective data to better understand the utility and productivity of a research fellowship. Methods: A national survey was conducted in which integrated plastic surgery residency applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
84
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 12 publications
4
84
2
Order By: Relevance
“…Research experience bolsters student applications leading to acceptance to higher tier plastic surgery residency programs. 28 With scholarly activity being a benchmark for acceptance into higher tier residencies, it is not surprising that the individuals graduating from these programs were more likely to pursue additional training, as fellowship training has been associated with future careers in academia. 4 Alternatively, these higher ranked residency programs may place more emphasis on academia and research therefore priming their resident graduates for academic pursuits.…”
Section: Discussionmentioning
confidence: 99%
“…Research experience bolsters student applications leading to acceptance to higher tier plastic surgery residency programs. 28 With scholarly activity being a benchmark for acceptance into higher tier residencies, it is not surprising that the individuals graduating from these programs were more likely to pursue additional training, as fellowship training has been associated with future careers in academia. 4 Alternatively, these higher ranked residency programs may place more emphasis on academia and research therefore priming their resident graduates for academic pursuits.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Thus, it is not unexpected that more applicants who have low Step 1 scores and who are not AOA members participate in research fellowships, as many believe that doing so will strengthen their residency application. 3,4,6 It is unclear, however, why such a large proportion of Asian applicants complete research fellowship, and more research exploring this finding is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…These results differ from Mehta et al's findings that Integrated Plastic Surgery applicants who completed research fellowships were significantly more likely to match than those who did not. 6 These contrasting findings may be a result of differences inherent to the two specialties or may be a result of differences in study design. Our study benefited from a large sample size and the direct analysis of residency applications rather than surveys, thus avoiding the effects of a small sample size or of response bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors noted that 63% of RGY applicants stated they pursued the RGY to strengthen their residency application. 8 A similar study in radiation oncology residency applicants found 33% of applicants did a RGY. Within orthopaedics, the incidence of applicants seeking RGYs, the reasons students are seeking these opportunities, and whether participating in a RGY leads to higher match success into orthopaedic surgery residency are unknown.…”
mentioning
confidence: 92%